Genes involved in hormone metabolism and cellular response in human ovarian granulosa cells - Brązert, M; Iżycki, D; Kranc, W; Borowiec, B; Popis, M; Ożegowska, K; Bręborowicz, A; Rachoń, D; Nowicki, M; Kempisty, B (Journal of biological regulators and homeostatic agents, 2019)
Endocrinal interactions are one of the most crucial regulatory mechanisms that maintain the state of homeostasis in humans. Processes such as oogenesis, folliculogenesis, menstruation and pregnancy remain under hormonal control. A key role in folliculogenesis is played by granulosa cells. Moreover, granulosa cells take part in corpus luteum formation after ovulation. Because of that, it is important to understand the ways in which the granulosa cells, associated with those processes, respond to hormonal stimulus. In the present study, a transcriptomic analysis of human granulosa cells (GCs) was carried out with the use of expression microarrays. The results were validated by RT-qPCR. The total RNA was isolated after 1st, 7th, 15th and 30th days of long-term primary cultures. The main focus of this work was placed on the genes belonging to "Response to estradiol", "Response to follicle-stimulating-hormone", "Cellular response to hormone stimulus", "Cellular hormone metabolic process" and "Hormone biosynthetic process" gene ontology groups. These groups of genes have been associated with GC hormone metabolism and cellular response to hormones. Eighty genes belonging to these groups were identified. Those that were members of more than one of the analyzed gene ontology groups, or exhibited unique expression patterns, were selected for further analysis. All of the selected genes were described, with their expression patterns detailed. In this manuscript, two gene expression patterns have been described. The first one showed large downregulation of genes in the later stages of culture, with the second one presenting upregulation of expression after day 1 of IVC. The present research was focused on six genes found to be the most important for steroidogenesis: STAR, POR, CYP11A1, ADM, GCLC, IL1B, as well as three genes of higher expression at the later stages of long-term in vitro culture: NR2F2, BMP4, COL1A1. The main goal of the presented study was to select genes involved in response to hormonal stimulus and hormone metabolism in GC long-term in vitro culture.
Keywords: ovulace; human granulosa cells; Granulosa Cells; folikulární buňky; Pregnancy; těhotenství; folikuly stimulující hormon; Estradiol; kultivované buňky; oogeneze; lidé; ženské pohlaví; Follicle Stimulating Hormone; ovariální folikul; Humans; hormone metabolism; cellular response; Cells, Cultured; Ovarian Follicle; Ovulation; Female; estradiol; Oogenesis